On the Political Epistemology of Female Circumcision in Africa - Ekong, Joseph T. (European journal of philosophy, culture and religion, 2022)
Purpose: The sensitization which this discussion engenders, has the objective of instituting an ever more formidable resilience in the advocacy against female genital mutilation (FGM) around the globe. Methodology: Besides the expository, analytic and evaluative character of this work, a particular effort is made to unveil the political and epistemological trappings that undergird the condemnable, but on-going practice of female genital mutilation in different parts of the world, especially in the continent of Africa. Findings: Some people point out that the word "cutting" is less judgmental and relates better to terms used in many local languages. However, many women's health and human rights organizations use the word "mutilation," not only to describe the practice, but also to point out the violation of women's human rights. Unique Contribution to theory, practice and policy (recommendation): Ritual circumcision of young males and females is a practice seen in many cultures across the world, including sub-Saharan and North Africa, the Muslim Middle East, the Jewish diaspora, Aboriginal Australia, the Pacific Islands, Southeast Asia, etc. This work discuses female circumcision as "female genital mutilation" and rejects the view proposed by some that its practice is culturally and ethically relative. All three terms, female genital cutting (FGC), female circumcision, or female genital mutilation (FGM) describe the procedure that cuts away part or all of the external female genitalia and are used to describe the same thing, that is, mutilation. Some people fear that parents may resent the implication that they are "mutilating" their daughters by participating in this largely cultural event, and so reject the term FGM in favour of FGC.